Актуальні питання досліджень сучасного стану природно-заповідної мережі басейну р. Вижівка (Правобережжя Прип’яті) - Павловська, Тетяна Сергіївна; Ковальчук, Іван Платонович; Василюк, Людмила Леонідівна; Pavlovska, Tetiana S.; Kovalchuk, Ivan P.; Vasilyuk, Liudmyla L. (Тернопільський національний педагогічний університет імені В. Гнатюка, 2013)
Стаття висвітлює результати досліджень природно-заповідного фонду (ПЗФ) басейну р. Вижівка, розташованого на правобережжі Прип’яті у Волинській області. Зокрема, проаналізовано структуру ПЗФ басейну, визначено ряд коефіцієнтів (заповідності території та інсуляризованості мережі, щільності заповідних об’єктів), виявлено особливості просторової локалізації природоохоронних територій, охарактеризовано проблеми й перспективи функціонування природно-заповідної мережі досліджуваного водозбору.

The article presents the results of the research of the natural preservation fund (NPF) of the Vyzhivka River, located on the right bank of the Prypyat River in Volyn region. The object of the research was the natural preservation fund of the Polissia Prypyat River. The subject of the research was the history of the development, the structure, the geospatial peculiarities, the problems and the perspectives of the functioning of the NPF of the Vyzhivka River. The article mentions the results of the previous research of the different aspects of the development and the state of the preservation in Volyn region. The article primarily points out the objects and areas of the natural preservation fund basin, the purpose being the research and defining of the level of the formation of the present natural and preservation network of the water collection and our assessment of the effectiveness of its functioning; it also has worked out a map and a chart which shows the regional distribution and the status of the natural and preservation areas; defines a range of rates (the preservation level of the area, the insularization of the network and the density of the preserved objects) it also reveals the peculiarities of the space location of the conserved territories. With the view to assess the influence of the natural condition of the basin of the River Vyzhivka and its economic development on the formation of the valuable natural objects, the paper calculated and defined the indices of the woodliness, marshiness, the length and the density of the transport network, the number and the area of the population centres, the arable level of the water collection area and the transformation of the river network. The work has compiled a list of the Red Book and the regionally rare plants growing on the territory of the region under consideration. Besides, the paper has explored the present structure of the natural and preservation fund of Volyn region; it has carried out the comparison of the above mentioned indices of the natural and preservation fund of the water collection of the Vyzhivka River with the corresponding indices of Volyn Region. In the conclusion the article analyses the problems and the perspectives of the functioning of the natural preservation network of the river basin under consideration.
The topical aspects of the research of the present state of the natural preservation network of the river Vyzhivka basin (The Right Bank of the Prypyat River)
Keywords: природно-заповідні території; природно-заповідний фонд; коефіцієнт заповідності; коефіцієнт інсуляризованості; щільність об’єктів ПЗФ; natural preservation areas; natural preservation fund; preservation rate; insularization rate; density of the NPF objects